2017
DOI: 10.1177/1971400917698980
|View full text |Cite
|
Sign up to set email alerts
|

Absent right common carotid artery associated with aberrant right subclavian artery

Abstract: Rarely, the external and internal carotid arteries arise separately from the brachiocephalic trunk and right subclavian artery (SA) or the aortic arch and reflect the absence of a common carotid artery (CCA). We report a 45-year-old man with absent right CCA associated with aberrant right SA, an extremely rare combination, diagnosed by computed tomography (CT) angiography during follow-up for postoperative aortic dissection. Retrospective careful observation of preoperative postcontrast CT revealed the absent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Absent right common carotid artery has rarely been described in the literature, usually as an incidental finding. [1][2][3] To our knowledge, this is the first case describing acute revascularization and stenting of such an artery, highlighting complete occlusion of variant anatomy as one potential challenge of acute endovascular interventions. 4…”
Section: Stroke Imagesmentioning
confidence: 99%
“…Absent right common carotid artery has rarely been described in the literature, usually as an incidental finding. [1][2][3] To our knowledge, this is the first case describing acute revascularization and stenting of such an artery, highlighting complete occlusion of variant anatomy as one potential challenge of acute endovascular interventions. 4…”
Section: Stroke Imagesmentioning
confidence: 99%
“…ere was one case of the bilateral origin of the ECA and ICA from the DAA [40], as cited [6], while there were two Uchino et al [46], Haughton and Rosenbaum's [47] case cited by Bryan [43], and one Weinberg's [48] case. ese cases were found in the patients or cadavers of both gender (37 of female, 24 of male and 26 of unknown sex), between the age of a newborn and 77 ( NAA: B+I+V+S [65] NAA: B+E+IV+S [38] NAA: B+E +E+I+S [55] F 5: Patterns of the branching of the normal aortic arch in cases of uni-and bilateral aplasia of the common carotid artery (CCA).…”
Section: Double Aortic Arch (Daa) and Interrupted Aortic Arch (Iaa)mentioning
confidence: 99%
“…Summarizing these data we have recorded 87 published and/or cited cases of the CCA aplasia in the last 233 years (1784-2017). This number was increased by four when we took into account the following cases: Nizankowski et al [94], as cited [32] have only reported the independent aortic origin of the left ECA and ICA as the type XIII without any additional data; Kunishio et al [53,95] reported the same case twice; Kobayashi et al [96] described the bilateral absence of the CCA and ICA, but they did not either mention the status of the ECAs; and Uchino et al [46] labeled the separated right ICA and ECA origin from "the BT" and not from the right CCA, although the right SA had the independent origin from the NAA.…”
Section: Collateral Pathwaysmentioning
confidence: 99%